Assessment of Nursing Staff Knowledge toward Disasters Management in Baghdad City Hospitals - Khaleel, Muna Abdulwahab (International Journal of Psychosocial Rehabilitation, 2020)
A disaster is an incident that can causes massive damage and disruption. Disasters are common worldwide event now a day. Nurses role are very important in disaster management and its recovery. The purpose of this study was to assess the nurses' knowledge regarding disaster management and emergency preparedness and to identify the availability of hospital specific plans regarding the disasters management as well as to determine the most important suggestions for improving disaster management. Quantitative cross sectional study design was used in this study. Semi structure Questionnaire was to collect the data. The questionnaires were administered by using convenient sampling. Data were statistically analyzed by descriptive criteria such as number, percentage, mean, median and standard deviation. The results of this study showed that participant nurses have a good knowledge on disaster management. Overall good knowledge was (61%). The conclusion of this study include that nurses knowledge about the disasters were good. There is need to work on the practice and knowledge as well in these two hospitals and in other health care settings. The study revealed that hospitals currently have deficiencies in disasters management. Further, follow up research are necessary for maximizing nursing education and nursing quality.